OCP Oracle Certified Professional Java SE 11 Developer Practice Tests: Exam 1Z0-819 and Upgrade Exam 1Z0-817 - Selikoff (Wiley Data and Cybersecurity, 2021)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies